ANALISIS ONLINE PROMOTION DAN ELECTRONIC WORD OF MOUTH PADA KEPUTUSAN PEMBELIAN PELANGGAN (Studi pada UMKM Diah Cookies di Kota Surabaya) - Rachmad Budi Laksono; Nuruni Ika Kusuma Wardhani (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyse the influence between Online Promotion and Electronic Word of Mouth on Customer Purchase Decisions for Diah Cookies MSME products in Surabaya. The background of this study stems from the increasing role of Digital strategies in shaping modern consumer behaviour, especially in the culinary sector, which is highly dependent on Online Promotion and customer reviews. Through this approach, the study seeks to identify the extent to which the effectiveness of Online Promotion and the power of e-WOM can encourage consumers to make purchasing decisions, while also providing an empirical overview of how MSMEs can optimise their Digital strategies to be more competitive in the era of internet-based Marketing. The research method used is a quantitative approach with an empirical design. Primary data was collected through an Online questionnaire using purposive sampling techniques from customers who had purchased Diah Cookies products. Data analysis was performed using the Partial Least Square (PLS) method, which allowed researchers to test the correlational relationship between variables simultaneously and measure the contribution of independent variables to purchasing decisions. Results of the study indicate that both Online Promotion and Electronic Word of Mouth have a positive and significant effect on Customer Purchase Decisions. An R-Square value of 0.758 indicates that these two Digital variables together can explain 75.8% of the variation in customer purchasing decisions. These findings emphasise the importance of consistent Online Promotion and positive e-WOM management to increase customer trust and loyalty to SME products such as Diah Cookies.